A justiça socioambiental e o direito ao desenvolvimento (sustentável): da dialética relação ao paradigma de reconstrução de um novo direito e justiça. - Balim, Ana Paula Cabral (2015)
This paper presents from the thesis that the Right to Development in a broad sense correctly nurtured in national law and international instruments, the opposite sense, does not lend itself to protect properly and effectively the various dimensions of which it is based. This law as post is distorted losing its essence to bow to the capitalist system of which it is part. This distortion of the Right to Development away from the ideal of Justice and gives rise to social and environmental context its major conflicts and injustices. Thus arises, given the gravity and considerable increase in social and environmental injustices and inequalities and the difficulty of resolving the legal post-conflict social Development, Environment and Society, an irremediable question: To what extent it is possible to achieve the ideal of Social and Environmental Justice without denying the Right to Development? It is established from then on the need to analyze the relationship between justice (social) environmental and (sustainable) development in the construction of a new environmental paradigm. To develop the theme, is used as the method of approach and procedure Dialectics. Structured through literature, and manipulated through production of reviews, abstracts and fichamentos work is composed in three parts, constituents of the dialectic such question, namely the Thesis, Antithesis and Synthesis. The first chapter presents the thesis statement as originally given, in the sense that, from a legal point of view, the development is a fundamental right. This law, in the context of a balance of power in the economic and political field became named "sustainable development", multidimensional concept that became part of numerous legal documents in the international and national level. The second chapter in antithesis to the first, opposes the thesis initially given, is that the reality points to the fact that the incorporation of the concept of sustainable development in different spheres: economic, political and legal has not realized to ensure justice in two dimensions: social and environmental - that is - a Social and Environmental Justice. Finally, the third chapter in the Synthesis dialectical conflict worked in the previous two chapters, the elements of this clash seeking the unity of the conflict for the construction of a new thesis work it, which is, that the social and environmental justice must be a (new) paradigm to unify both struggles for the right to sustainable development and to incorporate new dimensions to justice.